Preparation of preservative coating for tomatoes based on polyphenol modified chitosan and silver nanoparticles. (28th October 2022) - Huynh, Mai Duc; Linh, Nguyen Thi Dieu; Chinh, Nguyen Thuy; Trang, Nguyen Thi Thu; Manh, Vu Quoc; Linh, Nguyen Ngoc; Thang, Dam Xuan; Anh, Nguyen Thi Lan; Nam, Nguyen Tuan; Giang, Nguyen Vu; Trung, Vu Quoc
Abstract: This paper presents the modification of chitosan with polyphenols and application the modified chitosan in storage of tomatoes fruits. The ascorbic acid was used as a initiator for the modification reaction. The content of polyphenols was varied from 5 to 20 wt.% in comparison with chitosan weight. Some methods and techniques were used to characterize chitosan and modified chitosan including to infrared (IR) spectroscopy, DPPH assay and inhibition zone diameter by diffusion agar. The obtained results showed that chitosan was modified successfully with polyphenols. The modified chitosan samples have good antioxidant activity and against to E. coli, S. Aureus, and C. albicans . Based on the antioxidant activity and antimicrobial activity results, the most suitable content of polyphenols was found at 10 wt.%. The chitosan modified with 10 wt.% of polyphenols in a combination with nano Ag solution exhibits a significant efficiency on preventing the weight loss as well as remaining color, the firmness, and the soluble solids content (SSC) of tomato fruits during 20 days of testing. Moreover, the modified chitosan/nano Ag also has a great ability in inhibiting the growth of microbial on the skin of tomatoes during post‐harvesting storage. Abstract :